The Mawlid Tradition of Muhammad in Sudan - Mabrur, Muhamad Shofwan; Dou, Ahmad; Fadhlurrahman, M. Bintang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
Sufi in Sudan have the unique ways of preaching and spiritual practices, contributing to Sudan's reputation as the